2021
DOI: 10.1108/jcm-07-2020-3943
|View full text |Cite
|
Sign up to set email alerts
|

Shopping well-being: the role of congruity and shoppers’ characteristics

Abstract: Purpose Although shopping well-being has become a focal construct in retail shopping studies, little is known about the key drivers of this construct. This study aims to further discern some of the key antecedents of shopping well-being by particularly focusing on the role of congruity. Furthermore, the study explores whether shoppers’ demographic characteristics moderate the effects of congruity on shopping well-being. Design/methodology/approach Data were collected from a survey of actual shoppers in two u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…To compare the alternative model with the focal model on the suitability to exclude education as a moderator, as depicted in Table 7 , the study finds that the focal model is better than the alternative model given the values of AIC and BIC. The values of AIC and BIC of the focal model are higher than that of the alternative model as supported by previous studies [ 97 , 98 ]. In addition, as suggested by [ 83 ] that the EN score should be higher than 0.50, the focal model has an EN score higher than the EN value of the alternative model.…”
Section: Resultssupporting
confidence: 85%
“…To compare the alternative model with the focal model on the suitability to exclude education as a moderator, as depicted in Table 7 , the study finds that the focal model is better than the alternative model given the values of AIC and BIC. The values of AIC and BIC of the focal model are higher than that of the alternative model as supported by previous studies [ 97 , 98 ]. In addition, as suggested by [ 83 ] that the EN score should be higher than 0.50, the focal model has an EN score higher than the EN value of the alternative model.…”
Section: Resultssupporting
confidence: 85%
“…Secondly, the study investigated the role of self‐image congruity and sense of place in visitors' subjective well‐being. The findings revealed that visitors' self‐image congruity develops positive subjective well‐being (H5), reinforcing the recent findings of El Hedhli et al (2021). Additionally, sense of place was found to be positively and significantly related to subjective well‐being (H6), verifying the arguments of several scholars, such as Poe et al (2016) and Li and Chan (2020).…”
Section: Discussionsupporting
confidence: 88%
“…Characteristics of sharia products that are increasingly in line with consumer desires so that consumers feel the benefits that exist. These characteristics make the Islamic image of consumers to adjust sharia products as Muslims even more extraordinary, according to research by (El Hedhli et al 2021).…”
Section: Education Levelmentioning
confidence: 99%